From Bioengineering to CRISPR/Cas9 – A Personal Retrospective of 20 Years of Research in Programmable Genome Targeting - Jeltsch, Albert (Frontiers in Genetics, 2018)
Genome targeting of restriction enzymes and DNA methyltransferases has many important applications including genome and epigenome editing. 15-20 years ago, my group was involved in the development of approaches for programmable genome targeting, aiming to connect enzymes with an oligonucleotide (ODN), which could form a sequence-specific triple helix at the genomic target site. Importantly, the target site of such enzyme-ODN conjugate could be varied simply by altering the ODN sequence promising great applicative values. However, this approach was facing many problems including the preparation and purification of the enzyme-ODN conjugates, their efficient delivery into cells, slow kinetics of triple helix formation and the requirement of a poly-purine target site sequence. Hence, for several years genome and epigenome editing approaches mainly were based on Zinc fingers and TAL proteins as targeting devices. More recently, CRSIPR/Cas systems were discovered, which use a bound RNA for genome targeting that forms an RNA/DNA duplex with one DNA strand of the target site. These systems combine all potential advantages of the once imagined enzyme-ODN conjugates and avoid all main disadvantageous. Consequently, the application of CRISPR/Cas in genome and epigenome editing has exploded in recent years. We can draw two important conclusions from this example of research history. First, evolution still is the better bioengineer than humans and, whenever tested in parallel, natural solutions outcompete engineered ones. Second, CRISPR/Cas system were discovered in pure, curiosity driven, basic research, highlighting that it is basic, bottom-up research paving the way for fundamental innovation.